A composition-tunable ZnxCd1−xSe/ZnO core–shell nanowire array: mechanisms for the enhanced charge separation and its photovoltaic applications. Issue 15 (25th February 2015) - Cheng, Ke; Han, Xiao; Meng, Jian; Wang, Shujie; Du, Zuliang
<x xml:space="preserve">Abstract</x> The mechanism for enhanced charge separation was discussed and the charge transport model was established.